2016
DOI: 10.3402/gha.v9.31362
|View full text |Cite
|
Sign up to set email alerts
|

The Ugandan Youth Quality of Life index: assessing the relevance of incorporating perceived importance into the quality of life measure and factors associated with the quality of life among youth in slum areas of Kampala, Uganda

Abstract: BackgroundWhile quality of life (QoL) has long been an explicit policy goal for international development programmes, no instruments have specifically been developed for measuring health-related QoL in resource-limited settings. The aim of this study was to develop and validate a QoL instrument for use in international aid and development programmes and to assess factors associated with QoL among youth participating in a civic engagement project in Kampala.DesignUsing systematic random sampling, data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…volunteering for community committees). This finding is consistent with existing literature on interventions to improve psychological wellbeing of young people in low resource settings [ 19 , 55 – 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…volunteering for community committees). This finding is consistent with existing literature on interventions to improve psychological wellbeing of young people in low resource settings [ 19 , 55 – 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data collection questionnaire was based on previously validated instrument which had four areas: QoL; psychological wellbeing, self-esteem, the quality of neighbourhood social environment [ 25 ].The QoL instrument comprised 36 items, which we validated in previous studies using structural equation modelling and were found to have robust psychometric properties [ 19 ]. The QoL instrument had three sub-scales: social relations with internal consistency measured by a Cronbach’s alpha (α) of 0.86, living conditions (α = 0.84), and personal independence (α = 0.76).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of QOL broadly encompasses how an individual measures "goodness" of multiple aspects of their life 5 . Research directed to studying QOL has become increasingly important since the 1960's 6 and QOL is now a major factor to consider when instituting any form of therapy 7 . Several studies documented low levels of quality of life specifically because of having the stoma [8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Within Kampala, the two divisions of Nakawa and Makindye is where the research project was carried out. Over the past two decades these two divisions have been characterised by high unemployment in concert with a high dependence burden and rampant crime, which presents strong barriers to youth participation in community programmes and negatively affects their well-being [30]. Despite the dire economic and social situations that predispose youth to HIV, studies into their sexual behaviours, sexual education and access to contraceptive services, family planning, sexual consent as a right, and gender based violence are lacking.…”
Section: Introductionmentioning
confidence: 99%